2022
DOI: 10.3389/fnbeh.2022.856675
|View full text |Cite
|
Sign up to set email alerts
|

Implication of Extracellular Signal-Regulated Kinase in the Expression of Natural Reward: Evidence Not Found

Abstract: Many studies have implicated extracellular signal-regulated kinase (ERK) in drug-rewarding properties. Yet, only few investigated whether ERK also mediates the naturally rewarding stimuli. In this study, we compared ERK activation in the nucleus accumbens (NAc) after cocaine reward and after positive social interaction (SI) with a partner-reward in male rats. With our protocol, ERK phosphorylation in the NAc was not increased after cocaine reward. In addition, the interaction with a social partner did not alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…A recent study in male rats reported that 20 min following a conditioned place preference test that proceeded either social interaction conditioning or cocaine treatment did not result in a change in the phosphorylation of ERK1/2 in the nucleus accumbens [ 31 ]. However, a different study reported that 10 min following an acute social defeat experience in male mice there is an increase in the phosphorylation of ERK1/2 in the nucleus accumbens [ 32 ]. The increase in the phosphorylation of ERK1/2 was not observed 24 h following an acute social defeat.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in male rats reported that 20 min following a conditioned place preference test that proceeded either social interaction conditioning or cocaine treatment did not result in a change in the phosphorylation of ERK1/2 in the nucleus accumbens [ 31 ]. However, a different study reported that 10 min following an acute social defeat experience in male mice there is an increase in the phosphorylation of ERK1/2 in the nucleus accumbens [ 32 ]. The increase in the phosphorylation of ERK1/2 was not observed 24 h following an acute social defeat.…”
Section: Discussionmentioning
confidence: 99%